2020
DOI: 10.1523/eneuro.0405-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Expert Programmers Have Fine-Tuned Cortical Representations of Source Code

Abstract: Expertise enables humans to achieve outstanding performance on domain-specific tasks, and programming is no exception. Many studies have shown that expert programmers exhibit remarkable differences from novices in behavioral performance, knowledge structure, and selective attention. However, the underlying differences in the brain of programmers are still unclear. We here address this issue by associating the cortical representation of source code with individual programming expertise using a data-driven decod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 71 publications
(75 reference statements)
1
13
0
Order By: Relevance
“…Review of fMRI Studies of Programming Skills. To further evaluate the hypothesis that program understanding shares, the same resources as reading and/or calculation, one takes into account the results from the available fMRI studies using a program understanding task [7,24,30,32,33,[51][52][53]. These are, to our knowledge, the only studies available in the literature about the neuronal correlates of program understanding.…”
Section: Data Extractionmentioning
confidence: 99%
See 4 more Smart Citations
“…Review of fMRI Studies of Programming Skills. To further evaluate the hypothesis that program understanding shares, the same resources as reading and/or calculation, one takes into account the results from the available fMRI studies using a program understanding task [7,24,30,32,33,[51][52][53]. These are, to our knowledge, the only studies available in the literature about the neuronal correlates of program understanding.…”
Section: Data Extractionmentioning
confidence: 99%
“…These are, to our knowledge, the only studies available in the literature about the neuronal correlates of program understanding. The one from Castelhano et al uniquely reported functional and effective connectivity, but the amplitude findings of the available articles provide relevant insights on the relative weight of each network in programming tasks [2,30,32,33]. The work from Siegmund et al used detection of syntax errors as contrast condition to investigate the cognitive process of programming/source-code comprehension.…”
Section: Data Extractionmentioning
confidence: 99%
See 3 more Smart Citations